Prescription Drug Monitoring Programs and Other Interventions to Combat Prescription Opioid Abuse - Bharath Chakravarthy (Western Journal of Emergency Medicine, 2012)
The Center for Disease Control and Prevention (CDC) has published significant data and trendsrelated to opioid prescription pain relievers (OPR). In 2008, 20,044 deaths were attributedto prescription drug overdose of which 14,800 (73.8%) were due to OPR, an amount greaterthan the number of overdose deaths from heroin and cocaine combined. The majority of thesedeaths were unintentional. Between 1999-2008, overdose deaths from OPR increased almostfour-fold. Correspondingly, sales of OPR were four times greater in 2010 than in 1999. Mostsignificant to emergency physicians is the estimate that 39% of all opioids prescribed, administeredor continued come from the emergency department (ED). We present findings from theCDC’s Morbidity and Mortality Weekly Report (MMWR) with commentary on current recommendationsand policies for curtailing the OPR epidemic.1